Uji Sensitivitas Bakteri Staphylococcus aureus Terhadap Antibiotik pada Sampel Luka Pasca Operasi - Rahmat Budi Nugroho; D. Andang Arif Wibawa; Sallyvina Alifia (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2022)
Bacterial infection in wounds is still an important health problem and can affect length of stay and increase hospital costs. Wound infections, especially postoperative infections, can be caused by nosocomial infections. Infection in this wound can be caused by several bacteria, one of which is Staphylococcus aureus. The resistance of these bacteria to antibiotics is increasing. Because of this, this study aims to determine the resistance of Staphylococcus aureus bacteria to 6 antibiotics in postoperative wound samples. The method in this study was observational laboratory with a descriptive approach. The results of this study were that Staphylococcus aureus bacteria were sensitive to the antibiotics Ciprofloxacin, Clindamicin, Gentamicin and Rifampicin respectively by 60%, 80%, 70% and 80%. Of the 10 samples studied, Staphylococcus aureus bacteria were resistant to the antibiotics Amoxicillin by 60% and Erythromycin by 50%. Keywords: Sensitivity, Staphylococcus aureus, Antibiotics, Wounds